(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The sorption and desorption kinetics of cadmium immobilization in laterite soil using animal bones were investigated by subjecting the experimental data to various kinetic models. Sorption kinetic was studied with Pseudo first order, pseudo second order and parabolic diffusion while desorption kinetics was investigated with first order, Second order, and Simple Elovich Models. These models were chosen for their significance to understanding and optimizing the kinetics of immobilization processes, since they provide insights into the mechanisms driving sorption and desorption, allowing for the construction of more efficient systems. The SEM analysis of the bones show that they are mainly composed of calcium phosphate in the increasing order of CBA>PBA>HBA. This compound caused the precipitation of metal phosphate, which resulted in decreased mobility because of its low solubility. The physicochemical analysis of the soil shows that it contains iron oxide, which increased the iron and manganese oxide fraction of the soil, which resulted in increased bonding of metal to this fraction thus reducing the amount of metal available for plant uptake. The correlation coefficient R2 was used to determine the suitability of the model to the kinetic data. For pseudo first order, pseudo second order and parabolic diffusion, R2 ranges from 0.419-0.8295, 0.9946- 0.9997 and 0.5116- 0.8295 respectively while for desorption process, it ranges from 0.254-0.349, 0.164 – 0.211 and 0.981- 0.990 for first order, second order and Elovich models respectively for all amendments. This resultsimplied that pseudo second order model best suited the sorption process while desorption was best fitted...